SMA, GTA and P-GMA dissimilar weld joints of 304LN stainless steel to HSLA steel; Part -1: thermal and microstructure characteristics. (1st August 2018) - Anant, Ramkishor; Dahiya, Jag Parvesh; Agrawal, B P; Ghosh, P K; Kumar, Ravindra; Kumar, Sudhir; Kumar, Kaushal
Abstract: Fusion welding is one of the most commonly used processes used for the joining of dissimilar metals. Different fusion welding processes have varying degree of thermal impact affecting the characteristics of weld. The effect of thermal behaviour on microstructure of heat affected zone and weld have been carried out on shielded metal arc welded (SMAW), gas tungsten arc welded (GTAW) and pulse current gas metal arc (P-GMAW) welded AISI 304LN austenitic stainless steel and SAILMA/SA-543 high strength low alloy steel. The microstructure is correlated to mechanical properties of weld joints of different processes. The study reveals physical realisation of basic understanding and scientific knowledge gathered from the observations. Various aspects have been summarised by analysing critical the effects of different arc welding processes on microstructure of weld and HAZ zone.